Model Transparansi Penerimaan Pajak Daerah dan Retribusi Daerah pada Badan Pengelolaan Pendapatan Daerah Kabupaten Bogor - Girsang, Chrisna Delviana; Mulyadi; R. Djuaniarsono (Karimah Tauhid, 2024)
CHRISNA DELVIANA GIRSANG. NIM: E. 2010209. "Model of Transparency of Regional Tax and Regional Levy Revenue at the Regional Revenue Management Agency of Bogor Regency". Thesis. Legal Study Program, Faculty of Law, Djuanda University Bogor, 2024. Payment of regional taxes and regional levies originating from people’s money is a manifestation of community participation in financing national development, in its collection and management it must be transparent, professional and accountable and supported by a tax administration system that is easy for taxpayers to understand, so that it has an impact on increasing Regional Original Income. This research aims to examine the model of transparency in regional tax revenue and regional levies at the Regional Revenue Management Agency of Bogor Regency and its impact on public trust and increasing regional income. Transparency in public financial management, especially taxes and levies, is an important factor in realizing good governance. The research results show that the implementation of the transparency model in the receipt of Regional Taxes and Regional Levies at the Bogor Regency Regional Revenue Management Agency includes information accessibility, accountability and community participation. Regional governments that implement this transparency model are able to increase public trust, which in turn contributes to increasing taxpayer compliance and regional revenues. Obstacles faced in implementing transparency include limited human resources, information technology, and bureaucratic cultural resistance, so that the results have an impact on increasing Regional Original Income. The research method used is through a normative and empirical juridical approach with a literature approach using laws, regional regulations, and interviews. It can be concluded that the system and mechanism for monitoring regional tax collections and regional levies is still not running as effectively as expected. For this reason, with the authority of Regional Autonomy, regions can make regional regulations, especially regarding innovations in regional tax collection models and regional levies in accordance with the demographics of the region which will have an impact on the progress and empowerment of the region. Keywords: Transparency, Regional Tax, Regional Levy, Bappenda.